Numerical and Experimental Analysis of the Noise Generated in a Ducted Cavity Working in Various Conditions - Sebastian Rulik (MDPI AG, 2021)
Flow over a cavity or a gap may induce pressure fluctuations that are emitted as sound waves and perceived by a human as noise. This phenomenon may occur in different kinds of industrial machines or in everyday life devices, e.g., cars. For this reason, it is important to predict the flow conditions that intensify or attenuate the noise. This research paper presents the numerical and experimental analysis of the pressure fluctuations in a deep, ducted cavity. The experimental test stand made it possible to investigate the flow over a cavity with air velocity in the range of 30–80 m/s. The pressure fluctuations were measured using miniature microphones located in the duct and the cavity wall and processed with LabView software. The phenomena were also analysed using the computational fluid dynamics (CFD) technique. The several modelling approaches were tested and validated against the experimental data. The highest sound pressure levels were obtained for 40 and 70 m/s. The sound frequency increased with the flow velocity.